Implementation of Artificial Intelligence in the Teaching–Learning Process in Higher Education Institutions - Muñoz Paniagua, Kevin Francisco (Darul Yasin Al Sys, 2025)
This study analyzes the implementation of Artificial Intelligence (AI) in the teaching–learning process in higher education, a topic of growing significance due to its transformative potential in the educational field. The research addresses the problem of limited understanding regarding how AI is applied in higher education institutions, an issue of critical importance given its implications for students’ professional development. Adopting a qualitative approach grounded in the scientific method, the study employs a documentary research design, rigorously analyzing and synthesizing information from multiple scholarly articles. The findings identify the frequency and types of academic populations utilizing AI, the teaching, learning, and assessment activities in which AI proves beneficial, and the associated advantages, challenges, and difficulties of its integration into higher education. Data processing included analysis of tables and figures from selected sources, enabling the formulation of conclusions and recommendations that highlight key aspects of AI adoption and its potential to enhance educational practices.